Community development approach in the recovery of selected communities affected by typhoon Ondoy flood - Luna, Emmanuel M. (2011)
In September 2009, Metro Manila and the surrounding communities experienced the worst flood due to typhoons Ondoy and Pepeng. the depth of the flood reached 30 feet in some communities, submerging a number of urban poor areas. Along the Marikina River, residents were either relocated or allowed to stay in their communities. But those who were relocated to safer areas were confronted with new challenges due to problems in proximity and poor access to their sources of livelihood and the schools. Moreso, services for water, power and other basic provisions were inadequate. On the other hand, the people who stayed in the same vulnerable areas were able to immediately start rebuilding their houses and respective communities. Using the community development framework, this paper looks at the recovery and rebuilding of communities affected by the flood in two barangays: one that was relocated to another site; and another that stayed in the vulnerable community. The outcome shows the people who remained in the same community had a higher level of recovery compared to those in the relocation area. In this community, the residents had greater experiences in community education, organizing, resources and disaster risk management process.
Keywords: Community development -- Sta. Ana, San Mateo (Rizal); Community development -- San Jose, Rodriguez (Rizal); Emergency management -- San Jose,Rodriguez(Rizal); Emergency management -- Sta. Ana, San Mateo (Rizal); Floods -- Social aspects